P3 Exploring the impact of childhood cancer on educational achievement – a systematic review and meta-analysis. (May 2019) - Saatci, D; Thomas, A; Botting, B; Sutcliffe, A
Abstract : Aims: With remarkable progress in treating childhood cancer over recent years, more and more survivors are reaching adulthood and thus greater attention is being directed to understanding the late complications of surviving cancer, such as effects on educational attainment. Studies so far have provided conflicting results, emphasising the need for a systematic review and meta-analysis. In this first meta-analysis, we therefore aim to assess if any differences across educational outcomes exist in childhood cancer survivors compared to their peers. Methods: Medline, EMBASE, ERIC, CINAHL and PsycInfo were searched from inception to 1stMarch 2017. Any survivor with a diagnosis of childhood cancer was eligible. The primary outcome of interest was the level of educational attainment, classified into compulsory, secondary and tertiary levels. The secondary outcome was special educational needs. Subgroup analyses and meta-regression were carried out to assess heterogeneity. This study is registered with PROSPERO(CRD42017057501). Results: We identified 3231 publications through our search strategy. 26 studies were eligible for meta-analysis; which included 28 434 childhood cancer survivors, 17 814 matched-controls, 6582 siblings and six population studies from 11 developed nations across the globe. Overall, childhood cancer survivors appeared to be significantly less likely to progress onto secondary level education (pooled OR 1.36 (95% CI 1.26, 1.43, p <0.00001)) or to complete tertiary level education (pooled OR 0.87 (95% CI 0.78, 0.98, p =0.02)), compared to controls. They were also more likely to require special educational needs (pooled OR 2.47 (95% CI 1.91, 3.20, p <0.00001)) . Children who survived central nervous system tumours appeared to have worse outcomes compared to other types of cancers, although the latter also showed significantly poorer progression onto secondary level education (pooled OR 1.30 (95% CI 1.20, 1.41, p <0.00001, I 2 = 0%)). Conclusions: This is the first comprehensive meta-analysis, which explored educational attainment in childhood cancer survivors and elucidated overall poorer educational outcomes in survivors compared to peers. Poorer outcomes are sustained across different countries, implying that this is an international issue. Armed with these results, the next steps are to understand why childhood cancer survivors perform worse than their peers and how support can be targeted to ensure equal educational attainment.